Judicial Activism Hakim Peradilan Tata Usaha Negara Mewujudkan Kebersisteman Hukum Lingkungan Hidup - Sudarsono (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
Judicial activism, commonly translated as judicial activism or judicial engagement, is a philosophy in which judges make decisions by considering the development of legal consciousness and justice, or the latest developments in public policy. This writing aims to understand: 1) how Administrative Court judges implement judicial activism in realizing a legal system for environmental law, and 2) the position of Administrative Court decisions in realizing the environmental law system. This research is normative juridical in nature, using a statutory and conceptual approach, which will be analyzed descriptively and qualitatively. The results of the study show that: 1) Judges play a very important role in enforcing environmental law by realizing various rules for environmental management and protection in various environmental disputes in Administrative Court. The important role of judges in implementing the legal framework set out in legislation is crucial for protecting the environment. 2) The position of the Administrative Court's decisions in environmental disputes is highly strategic for two reasons: 1) From a legal scientific perspective, court decisions serve as: a source of law; the result of legal rule formulation; the transformation of abstract legal norms into actual law; the embodiment of checks and balances among branches of state power; and a reformer of the legal system. Therefore, without judicial decisions, the legal system would not function. 2) From a practical perspective, judicial decisions resolve concrete disputes and provide interpretations that determine what the law is.